2016
DOI: 10.1016/j.jjcc.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma heat shock protein 27 is increased in renal dysfunction and habitual smoking in a Japanese general population

Abstract: The present study demonstrated that HSP 27 levels were strongly related to renal dysfunction and habitual smoking in a dose-response manner in a Japanese general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
2
4
1
Order By: Relevance
“…Associations between antibodies, HSP, CVD risk and hypertension have been documented in several studies (Kocsis et al, 2002;Pockley et al, 2002;Zhang et al, 2008). However, biomarker studies in elderly patients are limited and mostly, non-exclusive (Bårdsen et al, 2016;Galović et al, 2016;Nakayoshi et al, 2016). In this present study, we were able to observe that anti-HSP60 plasmatic presences were associated with risk factors in the Framingham Score, one of the principal measurements for CVD in elderly patients.…”
Section: Discussionsupporting
confidence: 64%
“…Associations between antibodies, HSP, CVD risk and hypertension have been documented in several studies (Kocsis et al, 2002;Pockley et al, 2002;Zhang et al, 2008). However, biomarker studies in elderly patients are limited and mostly, non-exclusive (Bårdsen et al, 2016;Galović et al, 2016;Nakayoshi et al, 2016). In this present study, we were able to observe that anti-HSP60 plasmatic presences were associated with risk factors in the Framingham Score, one of the principal measurements for CVD in elderly patients.…”
Section: Discussionsupporting
confidence: 64%
“…Regarding the relationship between HSP27 and smoking, it has recently been shown that the plasma levels of HSP27 are higher in habitual smokers than in non-smokers and that the levels of plasma HSP27 in former smokers are almost within the normal range (35). Based on these present and previous findings, it seems that the temporary enhancement of phosphorylated-HSP27 release from human platelets after smoking cessation might be implicated in the deterioration of atherosclerotic pathophysiology through modulating inflammation progress.…”
Section: Discussionsupporting
confidence: 60%
“…Cigarette smoking is one of the most important causes of cardiovascular diseases acting via oxidative stress, [12] in which it has been demonstrated that smoking increases arterial stiffness, independent of blood pressure (BP). [13,14] Interestingly, smoking cessation more than a decade has been reported to recover arterial stiffness parameters to nonsignificant levels, [13] because smoking cessation reduces the levels of inflammatory markers such as C-reactive protein and fibrinogen.…”
Section: Introductionmentioning
confidence: 99%